Desain Prototype Sepeda Listrik Tiga Roda Sebagai Alat Transportasi Untuk Pengiriman Paket Di Kota Bekasi - Muhammad Irfan; Geggy Gamal Surya (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Electric bicycles have emerged as an efficient, environmentally friendly, and relevant transportation solution for urban communities. This study aims to design a three-wheeled electric bicycle specifically tailored for parcel delivery needs in Bekasi City. With the rise of e-commerce activities, the demand for fast and secure parcel delivery services has significantly increased. However, couriers using conventional motorcycles often face various challenges such as limited cargo capacity, range, and package security issues. Therefore, a three-wheeled electric bicycle is proposed as an innovative solution to address these challenges. This study employs a qualitative method involving in-depth interviews with couriers, logistics agency owners, and e-commerce users in Bekasi City. The results indicate that couriers require electric bicycles with a battery capacity capable of covering a minimum distance of 100-150 km per charge, as well as adequate cargo capacity to carry multiple packages simultaneously. Additionally, the need for a more extensive and easily accessible charging infrastructure also emerged as a key concern. The design proposed in this study includes a three-wheeled electric bicycle with secure and efficient package storage space, equipped with safety features for the rider. The implementation of the three-wheeled electric bicycle is expected to enhance the operational efficiency of parcel delivery, reduce environmental impact, and support the government's efforts in promoting eco-friendly vehicles.